The socio-economic burden of snakebite in Sri Lanka - Kasturiratne, Anuradhani; Pathmeswaran, Arunasalam; Wickremasinghe, A. Rajitha; Jayamanne, Shaluka F.; Dawson, Andrew; Isbister, Geoff K.; de Silva, Hithanadura Janaka; Lalloo, David G. (PLOS Neglected Tropical Diseases, 2017)
Background Snakebite is a major problem affecting the rural poor in many of the poorest countries in the tropics. However, the scale of the socio-economic burden has rarely been studied. We undertook a comprehensive assessment of the burden in Sri Lanka. Methods Data from a representative nation-wide community based household survey were used to estimate the number of bites and deaths nationally, and household and out of pocket costs were derived from household questionnaires. Health system costs were obtained from hospital cost accounting systems and estimates of antivenom usage. DALYs lost to snakebite were estimated using standard approaches using disability weights for poisoning. Findings 79% of victims suffered economic loss following a snakebite with a median out of pocket expenditure of 11.82 (IQR 2–28.57) and a median estimated loss of income of 28.57 and 33.21 for those in employment or self-employment, respectively. Family members also lost income to help care for patients. Estimated health system costs for Sri Lanka were 10,260,652 annually. The annual estimated total number of DALYS was 11,101 to 15,076 per year for envenoming following snakebite. Interpretation Snakebite places a considerable economic burden on the households of victims in Sri Lanka, despite a health system which is accessible and free at the point of care. The disability burden is also considerable, similar to that of meningitis or dengue, although the relatively low case fatality rate and limited physical sequelae following bites by Sri Lankan snakes means that this burden may be less than in countries on the African continent.